Removal of Congo Red from Aqueous Solution by Waste Banana Pith - Namasivayam, C.; Kanchana, N. (Universiti Putra Malaysia Press, 1993)
The ability of waste banana pith to remove Congo red from aqueous solution was investigated. Various parameters such as initial dye concentration, contact time, adsorbent dosage and pH effect were studied. The adsorption rate constant was found to be 1 X 10.1 min'} at 50 mg I-I dye concentration. Above 92% removal was observed in the pH range 2-11. The removal of dye by banana pith is mostly due to chemisorption.